Rural women reviving forgotten crops - Najjar, Dina; Amoak, Daniel (International Center for Agricultural Research in the Dry Areas, 2024)
Despite their vital contribution to agriculture, rural women frequently face significant barriers to accessing essential resources, including land, credit, and agricultural services. Yet they are vital to sustaining agri-food systems, particularly in the Global South. On International Day of Rural Women, we honor rural women for their invaluable contributions to advancing agriculture in the face of accelerating climate change.